Protocol analyses of cognitive strategies for reading comprehension in Malay and English - Siswahani Saban. (2009)
This study focussed on the mental processes bilingual readers used in reading comprehension by looking into the strategies used to comprehend a short story in English and Malay. The participants in this investigation were secondary 3 Malay Language students from the special and express streams. Data were collected using think aloud procedures. The readers' protocols in the form of audiotaped individual verbalizations were elicited from the subjects silent reading of a short story presented in Malay and English. The protocols, in both languages were transcribed and analyzed to infer strategies. Of the 9 strategies identified, 2 pertain to metacognitive; and 7 relate to cognitive aspects of reading. The frequencies of each of the strategies used (strategy total) by the readers were scored for both languages. Similarly, frequencies were also scored in terms of degree of diversity of strategies employed,